Breaking barriers and building bridges: the influence of ethics in advancing medical practice / Mark Kiak Min Tan ... [et al.] - Kiak Min Tan, Mark; Alvis, Wellester; Ab Manan, Muhammad Izwan; Chia, Wei Teoh (Faculty of Medicine, 2025)
About 30 years ago, Pellegrino published a seminal article titled "The Metamorphosis of Medical Ethics - A 30-Year Retrospective" that highlighted the growth and transformation of the field of medical ethics and predicted a rocky road ahead for this field due to it being a "subject of the widest public concern" [1]. It has also been widely acknowledged that every new medical innovation or advancement in science brings with it new ethical dilemmas, requiring a metamorphosis of ethical frameworks and solutions [1,2]. The advent of artificial intelligence in digital health, the impact of the COVID-19 pandemic on global health and migration, the influence of environmental ethics on climate change, and the move to decolonise bioethics to provide more nuanced and contextualised meaning to the field are just some current examples that highlight the influence and importance of well- grounded ethical thought in medical decision-making, leading to the further enlightenment and growth of medical ethics. Organisations that promote the field, such as the Southeast Asia Bioethics Network (SEABioN) [3] and Clinical Ethics Malaysia (CEM) [4], have also emerged both in Malaysia and the Association of Southeast Asian Nations (ASEAN) region.